Effect of Low Dose Intravenous Dexmedetomidine for the Prevention of Shivering Following LSCS Under Spinal Anaesthesia: A Randomised Control Trial - Megha Gandotra; Anju Jamwal; Anurati Raina; Sakshi Gupta (Dr. Annil Mahajan, 2023)
Background: Shivering is one of the most common side effects after cesarean section under neuraxial anesthesia due to inhibition of thermoregulatory control. However, it is often not treated. Aims & Objectives: This study aimed to evaluate the effect of low dose Dexmedetomidine on shivering in patients undergoing C-sections after spinal anesthesia. Materials & Methods: This randomized placebo controlled clinical study included 128 patients of ASA group II undergoing lower segment cesarean section under spinal anesthesia. They were randomly divided two groups as Group D received dexmedetomidine 20μg in 1ml normal saline intravenously and Group P received 1 ml of normal saline intravenously to all parturients after the clamping of umbilical cord. All patients were evaluated during and after surgery for hemodynamic changes, incidence of shivering, sedation score and any other side effects. Results: The incidence of shivering in group P (56.7%) was significantly higher than in group D (10%). The mean sedation score and hemodynamic changes were not significantly different between the two groups (P < 0.05). No significant adverse effects were noted. Conclusion: The administration of prophylactic intravenous low dose dexmedetomidine effectively reduces the incidence of perioperative shivering in patients undergoing lower segment cesarean section under spinal anesthesia without causing any remarkable side effects.